Stefan Zweig and world literature : twenty-first century perspectives - Vanwesenbeeck, Birger; Gelber, Mark H. (Studies in German literature, linguistics, and culture, 2014)
The twenty-first century has seen a renewed surge of cultural and critical interest in the works of the Austrian-Jewish author Stefan Zweig (1881-1942), who was among the most-read and -acclaimed authors worldwide in the 1920s and 1930s but after 1945 fell into critical disfavor and relative obscurity. The resurgence in interest in Zweig and his works is attested to by, among other things, new English translations and editions of his works; a Brazilian motion picture and a best-selling French novel about his final days; and a renewed debate surrounding the literary quality of his work in the London Review of Books. This global return to Zweig calls for a critical reassessment of his legacy and works, which the current collection of essays provides by approaching them from a global perspective as opposed to the narrow European focus through which they have been traditionally approached. Together, the introduction and twelve essays engage the totality of Zweig's published and unpublished works from his drama and his fiction to his letters and his biographies, and from his literary and art criticism to his autobiography